The Design and Evaluation of DACADE Visual Tool: Theoretical Implications - Madihah Sheikh Abdul Aziz; Gitte Lindgaard; Mohd Syarqawy Hamzah; T. W. Allan Whitfield (Bulletin of Electrical Engineering and Informatics, 2018)
A goal of every designer is to create successful products for consumers. In creating a successful product, it is crucial for a designer to understand consumers’ perceptions of a product early in the design process. Nevertheless, design students lack the necessary data collection and user testing skills to support effective design decision-making. Consequently, their products might not be acceptable to the intended consumers and are thus likely to fail in the marketplace. For design students to acquire those skills, design curricula should incorporate statistical courses teaching the concepts of data and user testing. We addressed this challenge by developing an automated visual tool named DACADE, assisting design students to systematically collect and analyze data. This paper reports the theoretical implications discovered during the process from designing through to implementing and evaluating DACADE concerning the transfer of learning, the appropriateness of graphics used in a software tool, and user motivation in a learning environment.